Emotional Intelligence and Social Skills Among Adolescents in Sidoarjo: Kecerdasan Emosional dan Keterampilan Sosial di Kalangan Remaja di Sidoarjo - Adellia Ikhsantinia Ashar; Lely Ika Mariyati (Academia Open, 2025)
General Background Adolescence represents a critical developmental stage characterized by increasing demands for emotional regulation and social interaction within school environments. Specific Background In senior high school students in Sidoarjo, social skills are considered essential for effective peer interaction and adjustment, while emotional intelligence is assumed to support emotional awareness and interpersonal behavior. Knowledge Gap Although numerous studies have examined emotional intelligence and social skills separately or within mediated frameworks, limited research has directly examined their statistical relationship among Indonesian adolescents in public senior high schools. Aims This study aims to examine the relationship between emotional intelligence and social skills among adolescents in Sidoarjo. Results Using a quantitative correlational approach with Spearman’s Rho analysis, the findings show a strong positive correlation coefficient numerically; however, the relationship is not statistically significant, indicating that emotional intelligence and social skills are not significantly related in the studied sample. Novelty This study provides direct empirical evidence from Indonesian senior high school adolescents showing a non-significant statistical relationship between emotional intelligence and social skills despite high levels of both variables. Implications The findings suggest that adolescent social skills may be associated with factors beyond emotional intelligence, providing a basis for further investigation into additional variables relevant to adolescent social development. Highlight: Statistical analysis showed no significant association between the two measured variables. Most participants demonstrated high levels across both measured constructs. Quantitative evidence indicates the presence of other contributing factors in adolescent social development. Keywords: Emotional Intelligence, Social Skills, Adolescents, Senior High School, Correlational Study